(3GdJfhjQ aj GdeUWdMGJ GdWHjIs - (3MSf Hf fhM GdbeQj, CHh efUhQ,fMh (B380 (3g`s
(3ChdgG (B:s
(3bGd CHh efUhQ Efi dcfg eYQaJi HaVd Yde GdWH Ydi SGFQ GdYdhe , hYdei HMGLI cd TNU ai cd hbJ s
(3BNQgG (B:s
(3MJi EPG LdS ajg hVY Ydjg GdWHb , hUGQ YfbI ai Pdc GdJbhjQ hQCSg NGQLkG efg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B224 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B299s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B57 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(2040(1)) s
Keywords: (3GdWHs